Literature - A Reflection of the Era (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the relationship between literature and the era in which it emerges and develops. The author examines how literary works reflect the spirit of the time, socio-cultural changes, ideological trends, and societal issues.Through the analysis of texts from different epochs, the author demonstrates how literature becomes a mirror of society, reflecting its values, conflicts, and aspirations. The article offers a profound look at the role of literature as a reflection of the era and its influence on shaping the cultural context and collective consciousness.